2022
DOI: 10.1111/gcb.16101
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting tolerance to ocean acidification: Insights from a new framework combining physiological and molecular tipping points of Pacific oyster

Abstract: Studies on the impact of ocean acidification on marine organisms involve exposing organisms to future acidification scenarios which has limited relevance for coastal calcifiers living in a mosaic of habitats. Identification of tipping points beyond which detrimental effects are observed is a widely generalizable proxy of acidification susceptibility at the populational level. This approach is limited to a handful of studies that focus on only a few macro-physiological traits, thus overlooking the whole organis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 93 publications
4
23
0
Order By: Relevance
“…In comparison, tissue growth is altered only by the OA effect on bioenergetics, which explains why the effect on shell may be observed before the effect on soft tissues. Nevertheless, at a longer time scale, soft tissues can be expected to be also affected by OA as described for C. gigas [87] and Spisula solidissima [20].…”
Section: Plos Climatementioning
confidence: 89%
“…In comparison, tissue growth is altered only by the OA effect on bioenergetics, which explains why the effect on shell may be observed before the effect on soft tissues. Nevertheless, at a longer time scale, soft tissues can be expected to be also affected by OA as described for C. gigas [87] and Spisula solidissima [20].…”
Section: Plos Climatementioning
confidence: 89%
“…Lutier et al (2022) found a relationship between pH level and feeding in the Pacific oyster and identified a tipping point of a pH of 6.9 [ 71 ]. It is important to consider a more extreme pH level may lessen the impact of increased food on resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, sessile bivalves must cope with the surrounding environmental conditions and therefore be able to respond and recover adequately from suboptimal conditions. Recently, we have shown that C. gigas juveniles are tolerant of a wide range of acidification levels, exhibiting a growth tipping point as low as pH 7.1 [29]. Here, we decipher the plasticity of oysters' growth when they return to ambient pH conditions and assess both the persistence of effects and their capacity for compensatory growth.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that (1) the weight differences below the tipping point would gradually fade after returning to ambient pH showing signs of compensatory growth (figure 1 a ), or that (2) weight differences would increase indicating persistent growth retardation (figure 1 b ). Theoretical models corresponding to these hypotheses were constructed from the data of [29].…”
Section: Methodsmentioning
confidence: 99%